1988
DOI: 10.1021/ic00274a039
|View full text |Cite
|
Sign up to set email alerts
|

Destabilizing d.pi.-p.pi. orbital interactions and the alkylation reactions of iron(II)-thiolate complexes

Abstract: Cl, CF3, N02) the -type interaction between formally occupied metal d orbitals and the sulfur lone pair that is principally 3p in character has been modeled with Fenske-Hall molecular orbital calculations and experimentally investigated by gas-phase photoelectron spectroscopy. A calculation for 1 (R = H) predicts that the highest occupied molecular orbital (HOMO) is metal-sulfur antibonding and largely sulfur in character. The observed HOMO ionization energies of 1 correlate with several chemical properties, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
77
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(85 citation statements)
references
References 4 publications
8
77
0
Order By: Relevance
“…The long Ru-S bond is due to the destabilizing filled-filled dp-pp orbital interaction between the p-type sulfur lone pair and the formally occupied metal dp orbitals of the Ru(II) low spin d 6 -centre, as sustantiated by FenskeHall molecular orbital calculations coupled with gas-phase photoelectron spectroscopy for CpFe thiophenolate complexes by Ashby et al [19].…”
Section: 320(2)-24155(8)mentioning
confidence: 96%
“…The long Ru-S bond is due to the destabilizing filled-filled dp-pp orbital interaction between the p-type sulfur lone pair and the formally occupied metal dp orbitals of the Ru(II) low spin d 6 -centre, as sustantiated by FenskeHall molecular orbital calculations coupled with gas-phase photoelectron spectroscopy for CpFe thiophenolate complexes by Ashby et al [19].…”
Section: 320(2)-24155(8)mentioning
confidence: 96%
“…The second steps of both paths apparently favor the same diastereoisomer. In the previously investigated series the rela tive configuration of the major diastereoisomer was in one case identified by X-ray crystallography as (R,R/S,S) [3], Compounds 7 and 8 do not provide any clear-cut spectroscopic handle from which the relative (7) or absolute (8 ) configurations of the two new stereocenters could be derived with certainty. The diastereoselectivity achieved in the oxidation of the bbpe complexes 6 a, b (eq (8 )) is similar to what we have found with the analogous (S,S)-CHIRAPHOS complexes [3].…”
Section: Discussionmentioning
confidence: 94%
“…Thiolate ligands are very strong a-and 7r-donors and as such are capable of stabilizing coordinatively unsaturated intermediates [8 ]. As a result, the substitution of adjacent ligands in low-valent transition metal complexes is greatly accelerated.…”
Section: Discussionmentioning
confidence: 99%
“…It should be observed that the monothioether complexes 4 are stable to further methyl addition. Finally, there is some evidence that the nucleophilicity of the sulfur atoms in the tris(thiolato)-bridged complexes 1 is restricted; for example, 1d does not react with soft alkylating agents (e.g., CH 3 I) though this reaction is generally observed for thiolate ligands bound to metal atoms which are in high oxidation states or are electron-deficient for other reasons [6].…”
Section: Resultsmentioning
confidence: 99%